REVIEW OF LUNG CANCER PATIENT CHARACTERISTICS AND TREATMENT STRATEGIES IN THE PANDEMIC COVID-19 YEAR Treated at the University Clinic of Radiotherapy and Oncology in Skopje - Simonida Crvenkova; Dragan Jakimovki; Vladimir Ristovski (Macedonian Academy of Sciences and Arts, 2023)
Introduction: It is estimated that delays in diagnosis due to the COVID-19 pandemic in North Macedonia could result in significant reductions in the number of potentially curative stages in lung cancer patients. Purpose: The aim of this study was to review patient characteristics and treatment strategies of lung cancer patients treated at the University Clinic of Radiotherapy and Oncology (UCRO), during the pre-pandemic year (from 1 of March 2019 to the end of February 2020) and the pandemic year (from 1 of March 2020 to the end of February 2021). Material: We analyzed eligible patients in the course of these two years according to patient characteristics and treatment strategies. Results: We have a record increasing in number of undefined lung cancer patients without any patho logical or histological conformation (11% pandemic year compared to 7% in the previous year), and an increased number of stage III and IV NSCLC patients in the pandemic year 449 (87%), in comparison to the pre-pandemic year of 403 (74%) patients. We have found a decreasing number of stage II NSCLC patients in the pandemic year 82 (13%) compared to 141 (26%) patients in the pre-pandemic year. We also note a decreasing number of patients with NSCLC operated on from 218 to 123 in the pandemic group. Due to frequent check-ups for COVID-19, we report an increasing number of early stage IA and stage IB patients, treated only by surgery. Conclusions: The strict screening and admittance criteria put in place by hospitals during the pandemic might have improved the oncology treatment course of lung cancer patients.
Keywords: COVID-19; lung cancer; pre-pandemic year; pandemic year